The viable but nonculturable state induction and genomic analyses of Lactobacillus casei BM‐LC14617, a beer‐spoilage bacterium. Issue 5 (6th July 2017) - Liu, Junyan; Li, Lin; Peters, Brian M.; Li, Bing; Chen, Lequn; Deng, Yang; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: This study aimed to investigate the viable but nonculturable (VBNC) state and genomic features of a beer‐spoilage strain, Lactobacillus casei BM‐LC14617. Induction on the VBNC state of L .  casei strain BM‐LC14617 was conducted by both low‐temperature storage and continuous passage in beer, and formation of VBNC state was detected after 196 ± 3.3 days and 32 ± 1.6 subcultures, respectively. Resuscitation of VBNC cells was successfully induced by addition of catalase, and culturable, VBNC, and resuscitated cells shared similar beer‐spoilage capability. Whole genome sequencing was performed, and out of a total of 3, 964 predicted genes, several potential VBNC and beer‐spoilage‐associated genes were identified. L .  casei is capable of entering into and resuscitating from the VBNC state and possesses beer‐spoilage capability. The genomic characterization yield insightful elucidation of VBNC state for L .  casei . This study represents the first evidence on VBNC state induction of L. casei and beer‐spoilage capability of VBNC and resuscitated cells. Also, this is the first genomic characterization of L. casei as a beer‐spoilage bacterium. The current study may aid in further study on L. casei and other beer‐spoilage bacteria, and guide the prevention and control of beer spoilage. Abstract : Lactobacillus casei is a common beer‐spoilage microorganism, and pose significant challenge for the brewing industry. This study represents the first evidence on VBNC induction and resuscitation of beer‐spoilage L .  casei and verification on beer‐spoilage ability of VBNC and resuscitated cells, as well as the first genomic characterization from beer‐spoilage L .  casei, further aids in the prevention and control for beer spoilage.